Supply Chain and Cost Management for Economic Sustainability of Future Market - Muljanto Siladjaja; Indra Siswanti; Hosam Alden Riyadh (International Journal of Supply Chain Management, 2020)
Abstract— This paper presents the impact of applying the supply chain management (SCM) on the earning field to optimize productivity and decreasing cost which will have a direct impact on the income in the market. By developing out the measurement of future prospect, this research have used the future market value as a new indicator, where the accounting information have a significant effect on an investment decision. This moderated multiple regression has used the dividend policy, where played a critical role in signaling communication. Thus, the causal research have the samples, that ammounted 154 the listed companies in the industrial manufacturing sector for the period 2015 until 2017. The result indicated that supply chain system has specified the SCM with cost prediction and given a practical guideline for the investor to estimate the future return with high accuracy. This dividend policy has minimized the pattern of opportunistic behavior in providing a misleading bias in the performance reporting when the dividend has strengthened the SCM positively on the future market value. By developing a a mapping with the decision model, that combined with Bayes Theorem, empirical research provides a brief illustration, pointed out the high quality financial statements have the implication of the game theory. This research recommended that this dividend policy can be used as a mandatory obligation, and the regulators must issue public policies. These findings offer new insights into the benefits and uses of power in supply chain relationships, in a previously unexplored context.